Resistance of Melons (Cucumis melo L.) to leafminers (Liriomyza spp.; Diptera: Agromyzidae - E. Gesmallah, Abd Elaziz; T. Yousif, Mohamed (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
The vegetable leafminers, Liriomyza spp. (Diptera: Agromyzidae ( are considered as one of the most important pests affecting vegetable crop production in many parts of the world. The reason why Liriomyza spp . are serious problems is the enormous build up of populations which are able to feed on a wide range of plant species. In the Sudan, two species of Liriomyza were reported: L. trifolii Burgess and L. sativae Blanchard' causing severe damage to a wide range of hosts. Recent surveys in central Sudan confirmed the existence of both species and that Liriomyza sativae was more common than L. trifolii on different host plants (Salah, 2001). The host range of L. sativae is confined to three families: Cucurbitaceae, Leguminaceae and Solanaceae, while L. trifolii is a polyphagous species, which attacks tomato, cucumber, lettuce, pepper and is also a serious problem on melons (Dogimont et al ., 1999).